Dyslipidemia in Myasthenia Gravis: A Systematic Review and Meta-Analysis - Vasileios Giannopapas; Vassiliki Smyrni; Georgia Papagiannopoulou; Stavroula Salakou; Dimitrios K. Kitsos; Ilianna Bethani; Christina Zompola; John S. Tzartos; Georgios Tsivgoulis; Sotirios Giannopoulos; Maria Kosmidou (Medicina)
Background and Objectives: Myasthenia Gravis (MG) comprises an autoimmune disorder marked by muscle weakness and fatigue. MG has been associated with comorbid conditions, including dyslipidemia (DL), which may exacerbate the clinical burden of MG and impact the overall quality of life. Materials and Methods: This systematic review and meta-analysis aimed to assess the prevalence of DL in patients with MG. Following PRISMA guidelines, a comprehensive search was conducted in the MEDLINE, Scopus, and Google Scholar databases. Primary outcomes included the pooled prevalence of DL in MG patients, and the relative risk of DL compared to healthy controls. Results: Nineteen studies involving 98,947 MG patients were analyzed. The pooled prevalence of DL was 23.64% (95% CI: 17.01–30.98). The relative risk of DL in MG patients versus controls was 1.13 (95% CI: 0.53–2.41), indicating no significant increase. Meta-regression revealed a positive correlation between DL prevalence and MG onset age (β = 0.02, p < 0.001), with a 2% rise in DL prevalence per 1-year increase in onset age. Regional subgroup analysis showed a statistical trend of higher DL prevalence in the USA (33.02%) compared to Asia (19.89%) and Europe (17.5%). Conclusions: This study found that approximately one in four MG patients has comorbid DL, with MG onset age significantly influencing DL prevalence. These findings highlight the need for personalized management strategies and evaluations (e.g., statins, LP(a) levels). Further research is warranted to elucidate the pathophysiological links between MG and DL.